Social practice on Facebook: Critical discourse analysis in the process of text production - Hetti Waluati Triana; Eka Putra Wirman; Martin Kustati; Reflinaldi Reflinaldi; Awliya Rahmi; Nelmawarni Nelmawarni (Universitas Syiah Kuala, 2020)
The study aims to identify the ways to produce text production process by Universitas Islam Negeri (UIN, or State Islamic University) students in Padang on Facebook. Documentations, observations, and in depth-interviews were used to collect data. There were 1,214 discourses found on group and personal accounts of 27 informants, and 400 discourses were taken as data of the research. The analysis was conducted by following Fairclough’s Critical Discourse Analysis, (CDA), with the Critical Linguistics approach. The research findings show that the text production process by UIN students on Facebook were done in three ways, namely producing their own text, spreading other people’s texts that are shared from the site, and producing text as a result of consumption of other texts. Producing text itself is a way of producing text by creating its own status as a form of expression of thoughts, feelings, and experiences, without referring to other texts or texts that have been published on other walls. The form of production by spreading text from other website is the most common form of text production. Production status is a form of the author’s reaction to the text he or she understood.